Proceedings of the Workshop on BioNLP 2007 Biological, Translational, and Clinical Language Processing - BioNLP '07 2007
DOI: 10.3115/1572392.1572406
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of caption search for bioscience journal search interfaces

Abstract: This paper presents the results of a pilot usability study of a novel approach to search user interfaces for bioscience journal articles. The main idea is to support search over figure captions explicitly, and show the corresponding figures directly within the search results. Participants in a pilot study expressed surprise at the idea, noting that they had never thought of search in this way. They also reported strong positive reactions to the idea: 7 out of 8 said they would use a search system with this kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…To some extent, this mimics the results of Hearst et al [13] who performed a user study on the viability of using caption searching to find relevant papers in the bioscience literature and found that “7 out of 8 [users] said they would use a search system with this kind of feature.” Only one user found that the alternative search engine returned better results. Half found SLIF better and more relevant, and the other three thought the results were not directly comparable.…”
Section: User Studysupporting
confidence: 76%
“…To some extent, this mimics the results of Hearst et al [13] who performed a user study on the viability of using caption searching to find relevant papers in the bioscience literature and found that “7 out of 8 [users] said they would use a search system with this kind of feature.” Only one user found that the alternative search engine returned better results. Half found SLIF better and more relevant, and the other three thought the results were not directly comparable.…”
Section: User Studysupporting
confidence: 76%
“…To some extent, this mimics the results of Hearst et al [13] who performed a user study on the viability of using caption searching to find relevant papers in the bioscience literature and found that "7 out of 8 [users] said they would use a search system with this kind of feature." Only one user found that the alternative search engine returned better results.…”
Section: User Studysupporting
confidence: 55%
“…They can fairly accurately form an opinion about the relevance of a publication to the clinical situation based on its title alone; however the title is not always sufficient in determining the evidence-based practice usefulness (henceforth evidence-based utility or clinical utility) of a publication [1]. There are indications that user experience can be improved by augmenting short bibliographic references with images [2].…”
Section: Introductionmentioning
confidence: 99%